Integrating Social Constructivism and Personal Construct Psychology Approaches: A Discourse Perspective - Fella Yorlanda (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2019)
This paper outlines the key features of discourse and psychological construct Psychology (PCP) in the past decades. This library research constructs its 59 related studies have been downloaded from the Google Scholar databases. The analysis in this study sees the crossroads between social constructivism and personal construct psychology (PCP) are increasingly being employs during the past decades. This convention is not only appropriate but seems to need each other. When construction sees cognition not as a person by any means leading to